Режим и эволюция полярных ледниковых покровов - Архипов С. М.; Бардин В. И.; Божинский А. Н.; Глазовский А. Ф.; Захаров И. Ю.; Игнатова И. Ю.; Константинова Т. Н.; Корякин В. С.; Красс М. С.; Ларина Т. Б.; Мачерет Ю. Я.; Троицкий Л. С. (СПб., Гидрометеоиздат, 1992)
Авт. указаны на обороте тит. л.